Do Positive Emotions Make You More Prosocial? Direct and Indirect Effects of an Intervention Program on Prosociality in Colombian Adolescents During Social Isolation Due to COVID-19 - Mesurado, Belén; Resett, Santiago; Tezón, Mariana; Vanney, Claudia E. (Frontiers in Psychology, 2021)
The objectives of this study are to analyze the efficacy of the Virtual Hero Program during the social isolation due to COVID-19 to increase the positive emotions (joy, gratitude, serenity, personal satisfaction, and sympathy) and prosocial behavior of Colombian adolescents. Additionally, we will analyze whether the Hero program, by directly promoting positive emotional states in adolescents, can predispose them to take prosocial actions towards other people (via an indirect or mediated effect). The final sample of the study comprised 100 participants from the intervention group (M age = 13.94, SD = .97) and 111 from the control group (M age = 14.39, SD = .81). The participants were assigned to the groups using a cluster randomized trial. The positive emotions questionnaire and the Kindness and Generosity subscale of the Values in Action Inventory of Strengths were used to measure the variables. The results indicated that the program increased joy, gratitude, serenity and personal satisfaction but not sympathy of those who participated in the intervention. The promotion of these positive emotions predisposed the Colombian adolescents to act prosocially. Furthermore, the program was also effective in directly promoting prosocial behaviors in the adolescents during social isolation, as observed through a statistically significant difference in the pre- and posttest evaluations between the control and intervention groups. The structure of the intervention brought adolescents closer to social situations to which isolation had limited their access, promoting the importance of closeness and solidarity with others within the complexities of the social confinement context. This study is particularly relevant because interventions with proven effectiveness are necessary to counteract the trauma produced by social isolation in young people throughout the world.